Metabolites of interest for food technology produced by microalgae from the Northeast Brazil - Sassi, Katharina Kardinele; Silva, João; Calixto, Clediana; Sassi, Roberto; Sassi, Cristiane Francisca (Revista Ciência Agronômica, 2018)
There is an increasing demand for bioprospection focusing on microalgae isolated from the northeastern region of Brazil with potential importance for food industries. To attend that need, we evaluated the characteristics of 12 regional species of microalgae grown under controlled cultivation conditions (temperature = 24 ± 1 ºC, illumination 150 µmol photons m-2 s-1, photoperiod of 12 h) in terms of their nutritional quality and lipid profiles. Significant differences in growth characteristics and chemical compositions were observed among the species investigated. High carbohydrate contents (> 25 g 100 g-1) were recorded in various strains of Chlorococcum and the marine microalga Amphidinium carterae; high protein contents (> 35 g 100 g-1) were observed in Scenedesmus acuminatus and Pediastrum tetras; and high lipid contents (> 25 g 100 g-1) in A. carterae and some strains of Chlorococcum sp. (cf. hypnosporum). Chlamydomonas sp. demonstrated the greatest production of carotenoids (64.92 mg g-1), chlorophyll-a (234.74 mg g-1), and chlorophyll-b (59.34 mg g-1). The lipid profiles of Chlorella cf. minutissima, four strains of Chlorococcum sp. (cf. hypnosporum), P. tetras, Planktothrix isothrix, and S. acuminatus indicated the presence of palmitic, oleic (ω-9), linoleic (ω-6) and α-linolenic (ω-3) acids, with more than 50% omegas in the total composition of their fatty acids. In terms of chemical nutrients, the microalgae cited were found to be potential sources of omegas, carotenoids, and chlorophylls that could be used in food industries.